PENERAPAN MODEL EXPERIENTIAL LEARNING BERBANTU MEDIA BENDA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SD - Poppy Ditha Hannesia; Heny Kusuma Widyaningrum; Siti Khuzaimah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT This research aims to apply the Experiential Learning model to enhance students' learning outcomes in Science focusing on the theme of Heat and Its Transfer, and to identify challenges in implementing this model along with corresponding solutions in the context of education. The study employed a collaborative classroom action research method conducted over two cycles, each comprising planning, implementation, observation, and reflection stages. Participants included teachers and fifth-grade students at Elementary School 02 Josenan during the academic year 2024/2025. The data analyzed consisted of qualitative information regarding the implementation of the Experiential Learning model and quantitative data concerning students' Science learning outcomes. The results indicate that employing the Experiential Learning model with phases such as Concrete Experience, Reflective Observation, Abstract Conceptualization, and Active Experimentation effectively improves students' learning outcomes in Science related to Heat and Its Transfer. The achievement rate increased from 76.33% in cycle I to 92.63% in cycle II. Challenges encountered included low student participation, difficulties in understanding the material, reluctance in presentation, lack of focus, and challenges in articulating opinions clearly. Solutions implemented included rewarding active student participation, enhancing guidance and supervision, assigning all group members to present discussion outcomes, and providing specific guidance in expressing opinions. Thus, this research demonstrates that the Experiential Learning model can effectively enhance Science learning outcomes at the elementary school level, despite facing several challenges that can be overcome with appropriate strategies. Keywords: Experiential Learning, Concrete Objects Media, Learning Outcomes ABSTRAK Penelitian ini bertujuan dalam menerapkan model Experiential Learning guna meningkatkan hasil belajar IPAS pada tema Panas dan Perpindahannya, serta untuk identifikasi kendala dalam menerapkan model tersebut beserta solusi pada konteks pembelajaran. Penelitian dilakukan dengan metode tindakan kelas kolaboratif yang terdiri dari dua siklus. Tiap siklusnya meliputi perencanaan, pelaksanaan, pengamatan, dan refleksi. Partisipan dalam penelitian ini ialah guru dan peserta didik kelas V di Sekolah Dasar Negeri 02 Josenan pada tahun ajaran 2024/2025. Data yang dianalisis terdiri dari data kualitatif terkait implementasi model Experiential Learning dan data kuantitatif berupa hasil belajar IPAs peserta didik. Hasil penelitian memperlihatkan yakni penggunaan model Experiential Learning dengan tahapan Concrete Experience, Reflective Observation, Abstract Conceptualization, dan Active Experimentation efektif dalam meningkatkan hasil belajar IPAS peserta didik pada tema Panas dan Perpindahannya. Tingkat ketuntasan belajar mengalami peningkatan yang semula 76,33% pada siklus I menjadi 92,63% pada siklus II. Kendala yang dihadapi meliputi tingkat partisipasi peserta didik yang rendah, kesulitan pemahaman materi, keengganan dalam presentasi, kurangnya fokus, dan hambatan dalam menyampaikan pendapat secara jelas. Solusi yang diimplementasikan mencakup pemberian penghargaan kepada peserta didik yang aktif, peningkatan bimbingan dan pengawasan, penunjukan seluruh anggota kelompok dalam presentasi hasil diskusi, serta bimbingan khusus dalam penyampaian pendapat. Dengan demikian, penelitian ini memperlihatkan yakni model Experiential Learning dapat efektif digunakan untuk meningkatkan hasil belajar IPAS di tingkat SD, meskipun menghadapi beberapa tantangan yang dapat diatasi dengan strategi yang tepat. Kata Kunci: Experiential Learning, Media Benda Konkret, Hasil Belajar